Parenthood and separation in couples 6 years after their first infertility consultation. (March 2016) - Ferreira, Magali; Sanchez, Emeline Teillet; Gatimel, Nicolas; Fajau, Carole; Lesourd, Florence; Bujan, Louis; Mieusset, Roger; Parinaud, Jean; Leandri, Roger
Abstract: Objective: To evaluate the percentage of couples achieving parenthood and the rate of separation 6 years after their first consultation for infertility. Study design: Epidemiological study in the reproductive medicine department of a French university hospital. All first consulting couples (FCC) who had their first infertility consultation in the department in 2007 were contacted by phone and asked to respond to a questionnaire concerning their infertility treatments, parenthood and marital status 6 years after their first consultation. Results: Of the 685 FCC, 94 could not be contacted, 34 refused to respond and 557 (86%) answered the questionnaire. Of 557 FCC who have responded, 361 (65%) have achieved parenthood: 166 (46%) after treatment, 98 (27%) after spontaneous conception, 38 (11%) after both spontaneous and treatment-induced conception and 59 (16%) through adoption. Parenthood was not influenced either by the causes or duration of infertility. Separation occurred in 53 (9.5%) of FCC, mainly in those without any children (28% vs 4% in FCC with at least one child; P < .0001). Conclusion: Six years after their primary consultation, 25% of couples remained childless and 28% of them were separated.